Analisis Indeks Kepuasan Pasien Rawat Jalan terhadap Kinerja Pelayanan Puskesmas Menteng di Kota Palangka Raya - Tri Lasmaria Sihotang; Mita Sari (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The purpose of this study was to measure the Index of Patient Satisfaction with Outpatient Installation Services in Menteng City Palangka Raya Health Center. With the Mix Method Method, where the quantitative calculation follows the guidelines of Permenpan Number 25 of 2004, where the indicator is used to see the level of community satisfaction with the elements of service (Permenpan Number 16 of 2014), which includes: 1. Compliance requirements, 2. Service procedures, 3. Timeliness of service, 4. Fairness of costs, 5. Results of service, 6. The ability of officers to provide services, 7. Courtesy and friendliness of officers, 8. Implementation of Service Notices/Service Promises, 9. Follow-up complaints that carried out by the service unit at the Menteng City Palangka Raya Health Center. In this study, the perception of the quality of outpatient installation services in the Menteng City Palangka Raya Health Center was perceived by the user community to be ranged between 62.51-81.25. The IKM values obtained are: on nine service elements = 80. Where the service element which is considered most satisfying by the respondent is Implementing Behavior or the attitude of the officer in providing service (NRR 3.47), Service Requirements (NRR 3.36), Service Notification NRR 3.31) and Cost/Tariff (NRR 3.27) whereas those that are considered unsatisfactory but still categorized as Good are elements of Service Time and Service Procedure (NRR 2.85 and 3.10). For this reason, efforts need to be made to improve the acceleration of service time and ease of community procedures in outpatient services.